2020
DOI: 10.29249/selcuksbmyd.783528
|View full text |Cite
|
Sign up to set email alerts
|

İşin Anlamlılığının Sapma Davranışı ve Performansa Etkisi

Abstract: İş, bireylerin günlük yaşamının önemli bir parçasıdır. İşe; psikolojik, sosyolojik ve ekonomik açıdan çeşitli anlamlar yüklenebilmektedir. Bu kapsamda; işin anlamlılığının örgütsel sapma ve iş performansına etkisini ortaya koymak üzere bir araştırma yapılmıştır. Veriler, literatürden yararlanılarak geliştirilen bir anket ile toplanmıştır. Anket; aktif iş yaşamında olan bireylere, 2016 yılının Mayıs-Haziran aylarında kolayda örnekleme tekniği ile uygulanmıştır. Veriler, tanımlayıcı istatistiklerin yanı sıra, aç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
0
0
1
Order By: Relevance
“…The studies conducted on teachers support the findings of this study, indicating that teacher absenteeism and failure to comply with working hours are indeed considered deviant behaviors. In contrast, it is observed that employees who embrace the organization's goals tend to develop a sense of organizational commitment, thereby avoiding deviant behaviors (Evcimen et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The studies conducted on teachers support the findings of this study, indicating that teacher absenteeism and failure to comply with working hours are indeed considered deviant behaviors. In contrast, it is observed that employees who embrace the organization's goals tend to develop a sense of organizational commitment, thereby avoiding deviant behaviors (Evcimen et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it led to negative attitudes from parents and external stakeholders towards the school. Previous studies have shown that organizational deviance in organizations can cause problems that hinder the achievement of organizational goals, such as damage to workplace reputation, decreased productivity, loss of motivation, and reduced organizational commitment, which may lead to employee turnover (Yıldız, 2013) (Avcı, 2008;Evcimen, Çakıcı & Çakıcı, 2020;Gürer, 2021;Robinson & Bennett, 1995;Tu et al, 2022;Uii, 2011). These findings align with the results of the research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eğer bütün veriler aynı ise standart sapma değeri sıfırdır. Eğer veriler ortalamadan uzakta yayılmış ise standart sapma değeri büyük ve eğer veriler ortalama değere yakın ise standart sapması küçüktür [21].…”
Section: Standart Sapmaunclassified
“…Bazı çalışmalarda ise işi anlamlı bulmanın sonuçları incelenmiş ve bunlara göre işini anlamlı bulan çalışanların daha fazla psikolojik iyi hal (Arnold vd., 2007;Passmore, Hemming, McIntosh, ve Hellman, 2020;Steger vd., 2012), işe adanmışlık (Jung ve Yoon, 2016;Steger vd., 2013), işe yönelik içsel motivasyon, öz yeterlilik ve örgütsel bağlılık (Jung ve Yoon, 2016;Leonardo vd., 2019;Steger vd., 2012), iş ve yaşam doyumu (Belwalkar, Vohra ve Pandey, 2018;Kamdron, 2005;Sparks ve Schenk, 2001;Spreizer vd., 1997;Steger vd., 2012;Wrzesniewski vd., 1997) ve iş performansı (Evcimen, Çakıcı ve Çakıcı, 2020;Özkan, 2017;Sigler ve Pearson, 2000) gösterdikleri bulunmuştur.…”
Section: İşin Anlamlı Bulunmasıunclassified